Institutional investors' distraction and executive compensation stickiness based on multiple regression analysis - Yizhao Hong; Chongyan Cao (Journal of Risk and Financial Management, 2023)
Based on the impact of industry extreme return on the attention of institutional investors, taking Chinese A-share listed companies from 2011 to 2020 as a sample, this paper empirically tests the relationship between institutional investors' distraction and executive compensation stickiness based on multiple regression analysis. The study finds that institutional investors' distraction promotes the executive compensation stickiness, which is more significant in the group of pressure-resistant institutional investors. The mechanism test finds that based on the governance effect, information effect and psychological effect, corporate external governance, stock price information content and management anxiety play a partial intermediary role between institutional investors' distraction and executive compensation stickiness. The moderating effect finds that the level of corporate internal governance and managerial overconfidence will weaken the impact of institutional investors' distraction on executive compensation stickiness. In addition, the distraction behavior in non-state-owned and western companies has a more significant economic impact.
Keywords: 650; executive compensation stickiness; governance effect; information effect; institutional investors’ distraction; multiple regression analysis; psychological effect